View of the dikapala Kubera in the Devakoshtha - Temples of India Project Team (Jio Institute, 2024)
Closer view of the dikapala (gods of cardinal directions) Kubera in the devakoshtha (niche) along the mandapa (pillared hall) dwarf walls of the Mahanaleshwar Temple. Kubera corresponds to the northern direction. The lower two hands of the deity are broken but the upper two hands hold a nakula (money) bag, one of the distinctive attributes of Kubera. The devakoshtha is composed of two slender pilasters surmounted by a miniature samvarna (pyramid-shaped) variety of shikhara (superstructure). The ghantas (bells) of the shikhara are fronted by a udgama (gavaksha or dormer window design). It rests on a low pedestal made up of multiple mouldings.